Para início de conversa - Bezerra, Sara Jane Cerqueira; Martins, Gleica Maria Correia; Neves, Jhonatan David Santos das; Almeida, Ricardo Santos de (Revista Interseção, 2021)
Revista Interseção, Palmeira dos Índios/AL, v. 2., n. 1, ago. 2020, p. 1-3.